PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS POWERPOINT PADA PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR - Padli Rahmadi; Sugiyono Sugiyono; Kartono Kartono (Universitas Tanjungpura, 2020)
Abstract This study aims to produce a validated powerpoint based instructional video media. The research method used is research and development (R&D) by adapting the Borg and Gall design development model. The data sources of this study were the results of observations, interviews, expert validation, student responses, and documentation during the use of powerpoint-based instructional video media. Data collection techniques in this study were observation, interviews and questionnaires. The results showed that the process of developing the powerpoint-based instructional video media had gone through 7 research steps, namely potential and problems, data collection, product design, product validation, revision, testing, and final product revision. The feasibility level of the instructional video media developed is very good in terms of design and material aspects with an average value of 3.76 and 3.57, and the results of product trials are very good with an average value of 3.58 . Keywords: Development, Learning Video Media, Powerpoint